Hợp đồng nhà thầu với chính phủ và khả năng tồn tại của doanh nghiệp trong đại dịch COVID-19 - Nguyễn Thu , Hằng; Vũ Thị Đan , Trà; Nguyễn Mạnh , Hiệp; Nguyễn Hoàng Minh , Trang (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
Using a firm-level dataset surveyed from 21 countries around the world provided by the World Bank before and during the COVID-19 pandemic, this paper examines the effect of government contract on firm’s survival. The results show that firms with government contracts are more likely to remain open during the pandemic. Additionally, government supports play a mediating role in this relationship. Specifically, firms with government contracts are more likely to receive government supports, and thus have a better chance to survive the pandemic. The authors discuss the implications of these findings for firm management and strategy.